Urinary Analysis of Four Testosterone Metabolites and Pregnanediol by Gas Chromatography-Combustion-Isotope Ratio Mass Spectrometry after Oral Administrations of Testosterone - Maître, Arnaud; Saudan, Christophe; Mangin, Patrice; Saugy, Martial (Journal of analytical toxicology, 2004)
The most frequently used method to demonstrate testosterone abuse is the determination of the testosterone and epitestosterone concentration ratio (T/E ratio) in urine. Nevertheless, it is known that factors other than testosterone administration may increase the T/E ratio. In the last years, the determination of the carbon isotope ratio has proven to be the most promising method to help discriminate between naturally elevated T/E ratios and those reflecting T use. In this paper, an excretion study following oral administration of 40 mg testosterone undecanoate initially and 13 h later is presented. Four testosterone metabolites (androsterone, etiocholanolone, 5α-androstanediol, and 5β-androstanediol) together with an endogenous reference (5β-pregnanediol) were extracted from the urines and the δ13C/12C ratio of each compound was analyzed by gas chromatography-combustion-isotope ratio mass spectrometry. The results show similar maximum δ13C-value variations (parts per thousand difference of δ13C/12C ratio from the isotope ratio standard) for the T metabolites and concomitant changes of the T/E ratios after administration of the first and the second dose of T. Whereas the T/E ratios as well as the androsterone, etiocholanolone and 5α-androstanediol δ13C-values returned to the baseline 15 h after the second T administration, a decrease of the 5β-androstanediol δ-values could be detected for over 40 h. This suggests that measurements of 5β-androstanediol δ-values allow the detection of a testosterone ingestion over a longer post-administration period than other T metabolites δ13C-values or than the usual T/E ratio approach.